2017
DOI: 10.1016/j.arthro.2017.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Commentary: All-Suture Anchors, Foam Blocks, and Biomechanical Testing

Abstract: Barber's biomechanical work is well known to Arthroscopy's readers as thorough, comprehensive, and inclusive of new designs as they become available. In "All-Suture Anchors: Biomechanical Analysis of Pullout Strength, Displacement, and Failure Mode," the latest iteration, Barber and Herbert test all-suture anchors in both porcine femurs and biphasic foam. While we await in vivo clinical trials that compare all-suture anchors to currently used anchors, Barber and Herbert have provided data to inform anchor choi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
5
1
Order By: Relevance
“…Differing results could also be explained by the discrepancy between the varying all-suture anchor systems. Even though the basic principle includes an expansion of the anchor and its locking underneath the cortex, significant differences have recently been reported [79,32]. Still, comparing the pullout strength of similar all-suture systems, the results of this study were superior to the ones reported by Nagra et al (247.2 ± 78 N vs. 145.8 ± 23.1 N).…”
Section: Discussioncontrasting
confidence: 65%
“…Differing results could also be explained by the discrepancy between the varying all-suture anchor systems. Even though the basic principle includes an expansion of the anchor and its locking underneath the cortex, significant differences have recently been reported [79,32]. Still, comparing the pullout strength of similar all-suture systems, the results of this study were superior to the ones reported by Nagra et al (247.2 ± 78 N vs. 145.8 ± 23.1 N).…”
Section: Discussioncontrasting
confidence: 65%
“…Both he and Brand 3 point out that all-suture anchors allow for smaller drill holes in the target bone. Brand also reminded us that all-suture anchors can cause bone reactions leading to cyst formation, 3 which is based upon the work by Pfeiffer et al, 4 who evaluated in vivo the 1.4-mm JuggerKnot. At 8 weeks, the JuggerKnot anchor tunnels were transformed into 6.3-mm cystic cavities, and the all-suture anchors showed significantly greater displacement than the control conventional anchor.…”
Section: See Related Article On Page 1954mentioning
confidence: 99%
“…In a recent editorial entitled "All Suture Anchors, Foam Blocks and Biomechanical Testing," Brand eloquently concluded that "biomechanical trials do not predict clinical feasibility." 5 So what impact will this information have on my practice? Does this study suggest that I should be using more anchors to repair my rotator cuffs, especially in osteoporotic bone?…”
Section: See Related Article On Page 377mentioning
confidence: 99%